Impact of an integrated electronic handover tool on pediatric junior medical staff (JMS) handover. (December 2017) - Cheng, Daryl R.; Liddle, James; Mailes, Emily; South, Mike
Highlights: Effective clinical medical handover ensures quality and safety of patient care. Significant variability in style, content and structure of clinical handovers currently exist. Electronic tools have been shown to assist in efficiency and accuracy of JMS handover. An integrated electronic handover tool improved JMS perceived handover efficiency via a reduction in redundant data entry. This was accompanied by improved JMS handover satisfaction. Abstract: Background: Clinical medical handover between doctors forms a critical part of the patient care process. However, with the evolution of junior medical staff (JMS) working conditions, time pressure and increasing clinical and administrative loads mean that quality clinical handover is increasingly important yet more challenging to achieve. This study evaluated the impact of a newly integrated electronic handover tool on JMS adoption and usage of the tool, as well as impacts on the quality (accuracy and redundancy) of handover data, JMS perceived workflow (time management and communication) and JMS satisfaction. Findings: The majority of JMS surveyed used the tool at 1 (87.0%) and 3 (67.4%) months post implementation. After the introduction of the electronic handover tool, 67.5% of users spent less than 15 min updating handover data in the electronic handover tool, compared to just 6.7% prior to the introduction. 28.3% of respondents noted that there was >25% redundant data, compared to more than half (52.2%) prior to introduction of the electronic tool. Overall JMS satisfaction with their handover process was significantly higher post implementation of the integrated electronic handover report (17.4% pre, 80.4% at 1 month, 67.4% at 3 months). Conclusion: A newly introduced integrated electronic medical record handover tool had a high uptake amongst JMS, and resulted in improvement in perceived handover efficiency, a reduction in redundant data entry and improved JMS handover satisfaction.